Structural identification and analysis of white tea anthocyanins - HU Jinxiang; YE Yushan; CAI Meisheng; ZHANG Qingbi; LI Bo; WU Yuanyuan; TU Youying; HE Puming (浙江大学学报. 农业与生命科学版)
The main anthocyanin components in white tea (Baihaoyinzhen, Baimudan, Gongmei and Shoumei) were preliminarily identified by high performance liquid chromatography-mass spectrometry, and then the composition characteristics and contents of anthocyanins were analyzed. The results showed that the main components of anthocyanins were delphinidin-3-O-galactoside, cyanidin-3-O-galactoside, pelargonidin-3-O-galactoside, cyanidin, delphinidin-3-O-[6-(Z)-p-coumarin] galactopyranoside, delphinidin-3-O-[6-(E)-p-coumarin] galactopyranoside, delphinidin-3-O-rutinoside, cyanidin-3-O-[6-(E)-p-coumarin] galactopyranoside and pelargonidin-3-O-rutinoside. The anthocyanin composition of Baihaoyinzhen, Baimudan, Gongmei and Shoumei was quite different. The anthocyanin contents of top grade and first grade of Baihaoyinzhen, top grade and first grade of Baimudan, first grade of Gongmei, and first grade and second grade of Shoumei were 83.80, 88.70, 90.59, 70.67, 122.75, 126.04 and 122.28 μg/g, respectively. The anthocyanin contents of Gongmei and Shoumei were significantly higher than those of Baihaoyinzhen and Baimudan. The above research results provide a scientific basis for the analysis of white tea anthocyanin components.